Zdarzylo sie nad jeziorem Mystic - Hannah, Kristin (Warszawa : Swiat Ksiazki, 2003)
Polish translation of "On mystic lake". Annie Colwater's marriage falls apart when her husband chooses a younger woman. Annie returns to her home town, Mystic, to try to revitalize her life.
"Nr. 4180"--T.p. verso.
Keywords: Divorced women -- Fiction; Widowers -- Fiction; Washington (State) -- Fiction